The Basic Psychological Need Satisfaction and Need Frustration at Work Scale: A Validation Study - Olafsen, Anja Hagen; Halvari, Hallgeir; Frølund, Claus Wiemann (Frontiers in Psychology, 2021)
The aim of the present study was to adapt and validate the Basic Psychological Need Satisfaction and Frustration Scale within self-determination theory (SDT) within the work domain. Confirmatory factor analyses of three Norwegian samples and one English sample as well as multi-group analyses to examine measurement invariance were performed. The results showed that the adapted work-related scale with its six-factor structure fitted the data well in all four samples, and partial measurement invariance was obtained across samples and languages. Furthermore, internal consistencies for the subscales were acceptable and the subscales predicted work-related correlates as expected, demonstrating the criterion validity of the scale. The current study contributes to a unifying measurement for future research on one of the central underpinnings of SDT within the work domain.